Covid-19 Pandemic: Revisit the Challenges and Sustainability of Homestays in Malaysia - Ramely, Asmahany; Mohamad, Zam Zuriyati; Mohamad Yusof, Nurul Afidah; Khor, Saw Chin; Mior Ahmed Shahimi, Wan Rozima; Oh, Alwin Jin Neng (UUM Press, 2023)
The Malaysian Ministry of Arts, Tourism and Culture (MOTAC) has been promoting homestay programs among the local community as a means to enhance quality of life and facilitate sustainable development. The community's distinct characteristics and cultural significance have effectively attracted the tourism sector and aligned with the 'Truly Asia' Campaign. However, the Covid-19 pandemic has had a global impact, leading countries to implement four phases of Movement Control Orders (MCOs). The objective of this study is to examine the difficulties encountered by homestay operators in maintaining the viability of their businesses in light of the Covid-19 pandemic, as well as to propose strategies aimed at securing the long-term sustainability of Malaysia's homestay programs. This qualitative study investigates the impact of the Covid-19 outbreak on homestay operators, focusing on their struggles with limited support and income, increased operational costs, and the toll on mental health. The study reveals key challenges based on data from in-depth interviews conducted with operators in states with high Covid-19 cases. The respondents provided insights into various strategies employed to ensure the long-term viability of Malaysia's homestay programs, including diversification, business restructuring, government support, and digital marketing. This research contributes to the government's efforts to promote homestay programs in the tourism industry, shedding light on the industry's resilience during challenging times.